Social dysfunction in Ecuadorian, Peruvian, and Venezuelan media workers - Byron Fernando Bustamante-Granda; Claudia Torres-Montesinos; Jhon Remigio Espinosa-Iñiguez (PLOS Mental Health, 2026)
The personal, occupational and psychosocial risk and protection factors associated with social dysfunction in media workers are analyzed. A total of 314 workers were surveyed. Data were collected on personal and occupational variables, and scales were administered to assess coping styles, perceived loneliness, emotional impact of the health emergency, and social dysfunction, which was measured using Scale C of the General Health Questionnaire (GHQ-28). It was found that 19.7% were at risk of social dysfunction. This risk was particularly evident among workers without a formal partner and those performing fieldwork in peripheral cities. Bivariate analyses indicated that workers at risk were more likely to be women, younger, less experienced, with limited training during the crisis, and reported poorer health, lower perceived ability to cover risky events, greater concern about infecting their families with COVID-19 or dying, and a stronger desire to quit their jobs. Psychosocially, they experienced greater emotional impact, higher levels of loneliness, greater use of self-blame and behavioral disengagement, and less use of active coping. The final logistic regression model correctly classified 89.8% of cases. Factors associated with increased odds of social dysfunction included desire to change jobs, perception that health would not improve, concern about infecting their families with COVID-19, hyperconnectivity, and use of planning. Factors associated with lower odds included working in the capital city, seeking emotional support, and employing humor. The importance of preventing social dysfunction to improve the mental health and general well-being of media workers in crisis contexts is discussed. In summary, the social dysfunction in media workers increases with personal or family affectation, the desire to change employment, hyperconnectivity, planning, and self-blame, and decreases among those who work in the capital, seek emotional support, and use humor.